2021
DOI: 10.1016/j.omtm.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible immortalization of erythroblasts from multiple stem cell sources provides approach for sustainable RBC therapeutics

Abstract: Developing robust methodology for the sustainable production of red blood cells in vitro is essential for providing an alternative source of clinical-quality blood, particularly for individuals with rare blood group phenotypes. Immortalized erythroid progenitor cell lines are the most promising emergent technology for achieving this goal. We previously created the erythroid cell line BEL-A from bone marrow CD34 + cells that had improved differentiation and enucleation potential compared to other lines reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…BEL-A cells 66 , 67 , established in the lab of Deborah E. Daniels and Jan Frayne, were cultured in StemSpan™ SFEM (Stemcell Technologies) containing 50 ng/mL SCF, 3 U/mL EPO, 1 μM dexamethasone, and 1 µg/mL doxycycline. To induce erythroid differentiation, expanding cells were transferred to primary medium supplemented with 1 µg/mL doxycycline for 4 days, and for a further 4 days without doxycycline.…”
Section: Methodsmentioning
confidence: 99%
“…BEL-A cells 66 , 67 , established in the lab of Deborah E. Daniels and Jan Frayne, were cultured in StemSpan™ SFEM (Stemcell Technologies) containing 50 ng/mL SCF, 3 U/mL EPO, 1 μM dexamethasone, and 1 µg/mL doxycycline. To induce erythroid differentiation, expanding cells were transferred to primary medium supplemented with 1 µg/mL doxycycline for 4 days, and for a further 4 days without doxycycline.…”
Section: Methodsmentioning
confidence: 99%
“…Recent progress supports the translatability of such an approach, including work by clinical stage companies to engineer donor human CD34 + hematopoietic stem cells via lentiviral transduction to generate therapeutic RBCs and engineered GPA-based eRBCs . Others have generated immortalized CD34 + cell lines for the production of human erythrocytes from bone marrow, cord blood, and peripheral blood. , Together, these research avenues are exciting potential advances in eRBC technology that could be enabled by the foundations established in this study.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, we revealed that immortalized erythroid cells are damaged via γ‐irradiation and almost eliminated by leukoreduction filters, but these methods are not completely safe. HPV16 E6/E7 ‐transduced erythroid cell lines have abnormal karyotypes 15 ; thereby, increasing the risk of tumorigenesis if even one transduced cell persists. A recent study found that the double filtration method for blood products can reduce residual leukocyte levels.…”
Section: Discussionmentioning
confidence: 99%